Resilience in the mining context: emergence, adaptation and strengthening of traditional miners in some municipalities of Chocó, Colombia - Perea-Lemus, Betty-Leonor (2024)
Introduction: Despite the historical, cultural and economic importance of mining in Chocó, Colombia, there is a notable lack of research focused on understanding the more traditional expressions of this activity. This article analyzes resilience in the context of traditional mining in the municipality of Unión Panamericana in that region. Objective: This study examines and analyzes the existing literature on resilience in the lives of traditional miners and its contribution to their adaptation and strengthening in this particular context. The literature is reviewed from individual, community and ecological perspectives of resilience. The community perspective highlights the importance of resilience in strengthening social cohesion, citizen participation and cultural identity around community needs. On the other hand, the ecological perspective highlights the interconnection between human beings and their environment, influencing their capacity to adapt and recover. Methodology: The methodology is based on a systematic literature review in databases and university repositories. Conclusions: Finally, this article offers a significant contribution to academic knowledge on resilience and its applicability in specific contexts, such as that of traditional miners in Unión Panamericana, Chocó, Colombia.